Time to Push: Use of Gestational Age in the Electronic Health Record to Support Delivery of Relevant Prenatal Education Content. Issue 2 (20th April 2017) - Arcia, Adriana
Introduction: Clinicians must provide anticipatory guidance pregnant clients would find useful but might not seek out independently. Client-facing health information resources should a) satisfy clients' health self-management queries, and b) provide anticipatory guidance at developmentaly appropriate times. Care Guide (by our technology partner, Maternity Neighborhood™) is an online maternity education platform positioned to meet pregnant clients' information needs through high-quality, curated content paired with secure provider/client messaging. The research version of Care Guide is called Maternity Information Access Point (MIAP). Little is known about how clients perceive or engage with maternity education delivered via patient portal or personal health record. Methods: This qualitative study employed focus groups and four week field-testing periods with English- and Spanish-speaking pregnant women enrolled in Medicaid. User satisfaction and system usability were evaluated through self-report instruments. Results: Twelve of the 16 participants logged usage of MIAP, with amount of usage varying widely. Satisfaction (4.3/5) and usability (4.7/5) were rated highly. Weekly content push emails were a popular feature; participants agreed the content was relevant, timely, and useful. Forgetting passwords and lack of experience with technology were barriers to use. Discussion and Conclusion: Gestational age captured in the electronic health record can support automated pushing of content containing highly relevant anticipatory guidance. Platform features that guide the user through content can be leveraged to promote continued user engagement. Users' desire for easy access to content must be balanced against the need to safeguard protected health information. Digital newcomers may require in-person technical support.